Synthetic gas catalyst and preparation method and application thereof
By using SAPO-34 molecular sieve and TiO2-doped ZnCr2O4 in the synthesis gas catalyst, the problem of low CO conversion in existing catalysts was solved, and the effects of high CO conversion and low carbon olefin selectivity were achieved.
Patent Information
- Application Number
- CN202411933172.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The existing OX-ZEO bifunctional catalyst has a low CO conversion rate in the synthesis gas olefin reaction, which limits the high selective production of low-carbon olefins.
The synthesis gas catalyst including SAPO-34 molecular sieve and TiO2-doped ZnCr2O4 is used to refine the grain size of ZnCr2O4 by controlling the doping amount of TiO2, improve its dispersion and specific surface area, thereby improving the CO conversion rate and selectivity of low-carbon olefins.
The CO conversion rate is greater than 25% and the selectivity of C2=~C4= is greater than 80%, which significantly improves the low-carbon olefin selectivity of the synthesis gas catalyst.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of synthesis gas catalysis, and in particular to a synthesis gas catalyst and a preparation method and application thereof. Background Art
[0002] At present, the new synthesis route of OX-ZEO bifunctional catalyst in the technology of preparing light olefins from synthesis gas can synergistically couple the methanol / dimethyl ether synthesis reaction and the CC coupling reaction, breaking through the limitation that the Fischer-Tropsch synthesis products obey the ASF distribution, and directly obtaining light olefins with high selectivity, becoming a light olefin production technology route with great development prospects.
[0003] The key to the research on OX-ZEO bifunctional catalyst for syngas to olefins is the development of efficient and stable catalysts. x / MSAPO bifunctional catalyst is used for the direct production of low-carbon olefins from syngas, achieving a breakthrough in the production of olefins from syngas, with a CO conversion rate of 17% and C2 = -C4 = The selectivity of CH4 and C 5+ The selectivity of hydrocarbons was less than 5%, and the catalyst maintained a fairly high stability. During the 110h reaction period, the CO conversion rate and the selectivity of light olefins only decreased slightly. In another related study, the ZnO-ZrO2 / SAPO-34 bifunctional catalyst prepared was used for the direct production of light olefins from syngas, with a CO conversion rate of 11% and C2 = -C4 = The selectivity of CH4 and C 5+ The selectivity of hydrocarbons is kept at a very low level.
[0004] Although a large number of OX-ZEO bifunctional catalyst preparation studies have been proposed, the CO conversion rate in the synthesis gas to olefins reaction catalyzed by bifunctional catalysts is still low. Summary of the invention
[0005] The object of the present invention is to provide a synthesis gas catalyst and a preparation method and application thereof. The synthesis gas catalyst provided by the present invention has high CO conversion rate and low carbon olefin selectivity when used in the synthesis gas to produce low carbon olefin reaction.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a synthesis gas catalyst, comprising SAPO-34 molecular sieve and TiO2-doped ZnCr2O4;
[0008] The molar ratio of Zn element, Cr element and Ti element in the TiO2-doped ZnCr2O4 is (4.5-5.5): (9-11): (0.5-2);
[0009] The mass ratio of the SAPO-34 molecular sieve to the TiO2-doped ZnCr2O4 is 1:(0.8-1.1).
[0010] The present invention also provides a method for preparing the synthesis gas catalyst described in the above technical solution, comprising the following steps:
[0011] (1) mixing zinc salt, chromium salt, TiO2 and water to obtain a mixed solution;
[0012] (2) mixing the mixed solution obtained in step (1) with a precipitant to carry out a co-precipitation reaction, and then aging and calcining in sequence to obtain TiO2-doped ZnCr2O4;
[0013] (3) Mixing the SAPO-34 molecular sieve and the TiO2-doped ZnCr2O4 obtained in step (2) to obtain a synthesis gas catalyst.
[0014] Preferably, in step (1), the volume ratio of the amount of zinc salt, the amount of chromium salt, the amount of TiO2 and water is (4.5-5.5) mol: (9-11) mol: (0.5-2) mol: (28-32) L.
[0015] Preferably, the precipitant in step (2) is sodium carbonate or ammonium carbonate.
[0016] Preferably, the precipitant is used in the form of a solution.
[0017] Preferably, the concentration of the precipitant in the solution is 0.4-0.7 mol / L.
[0018] Preferably, the temperature of the coprecipitation reaction in step (2) is 50-80° C., and the pH value of the coprecipitation reaction is 5.5-8.5.
[0019] Preferably, the aging temperature in step (2) is 50-80° C., and the aging time is 0.5-4 h.
[0020] Preferably, the calcination temperature in step (2) is 400-600° C., and the calcination time is 3-5 hours.
[0021] The present invention also provides the use of the synthesis gas catalyst described in the above technical solution or the synthesis gas catalyst prepared by the preparation method described in the above technical solution in preparing light olefins from synthesis gas.
[0022] The synthesis gas catalyst provided by the present invention comprises SAPO-34 molecular sieve and TiO2-doped ZnCr2O4; the mass ratio of the SAPO-34 molecular sieve and the TiO2-doped ZnCr2O4 is 1:(0.8-1.1); the molar ratio of the Zn element, the Cr element and the Ti element in the TiO2-doped ZnCr2O4 is (4.5-5.5):(9-11):(0.5-2). The present invention dopes TiO2 into ZnCr2O4. By controlling the doping amount of TiO2, the grain size of ZnCr2O4 can be refined, the dispersibility of the effective active component (ZnCr2O4) is improved, and the specific surface area and total pore volume of TiO2-doped ZnCr2O4 are increased, thereby improving the CO conversion rate and low-carbon olefin selectivity of the synthesis gas catalyst; SAPO-34 molecular sieve is used, and the ratio of SAPO-34 molecular sieve and TiO2-doped ZnCr2O4 is controlled to further improve the low-carbon olefin selectivity of the synthesis gas catalyst. The results of the embodiment show that the synthesis gas catalyst provided by the present invention has a CO conversion rate of more than 25%, and a C2 = ~C4 = The selectivity is greater than 80%, with high CO conversion rate and high light olefin selectivity. DETAILED DESCRIPTION
[0023] The invention provides a synthesis gas catalyst, comprising SAPO-34 molecular sieve and TiO2-doped ZnCr2O4.
[0024] In the present invention, the molar ratio of Zn, Cr and Ti in the TiO2-doped ZnCr2O4 is (4.5-5.5): (9-11): (0.5-2), preferably (4.7-5.2): (9.5-10.5): (0.8-1.5); more preferably 5:10:1. The present invention limits the molar ratio of Zn, Cr and Ti in the TiO2-doped ZnCr2O4 to the above range, so that TiO2 can have a suitable ratio, refine the grain size of ZnCr2O4, improve the dispersibility of the effective active component (ZnCr2O4), and at the same time improve the specific surface area and total pore volume of TiO2-doped ZnCr2O4, thereby improving the conversion rate of CO and the selectivity of light olefins of the synthesis gas catalyst.
[0025] In the present invention, the mass ratio of the SAPO-34 molecular sieve to the TiO2-doped ZnCr2O4 is 1: (0.8-1.1), preferably 1: (0.9-1.0), and more preferably 1: 1. The present invention limits the mass ratio of the SAPO-34 molecular sieve to the TiO2-doped ZnCr2O4 to the above range to further improve the low-carbon selectivity of the synthesis gas catalyst.
[0026] The present invention dopes TiO2 into ZnCr2O4, and by controlling the doping amount of TiO2, the grain size of ZnCr2O4 can be refined, the dispersibility of the effective active component (ZnCr2O4) is improved, and the specific surface area and total pore volume of TiO2-doped ZnCr2O4 are increased, thereby improving the CO conversion rate and low-carbon olefin selectivity of the synthesis gas catalyst; SAPO-34 molecular sieve is used, and the ratio of SAPO-34 molecular sieve and TiO2-doped ZnCr2O4 is controlled, so as to further improve the low-carbon olefin selectivity of the synthesis gas catalyst.
[0027] The present invention also provides a method for preparing the synthesis gas catalyst described in the above technical solution, comprising the following steps:
[0028] (1) mixing zinc salt, chromium salt, TiO2 and water to obtain a mixed solution;
[0029] (2) mixing the mixed solution obtained in step (1) with a precipitant to carry out a co-precipitation reaction, and then aging and calcining in sequence to obtain TiO2-doped ZnCr2O4;
[0030] (3) Mixing the SAPO-34 molecular sieve and the TiO2-doped ZnCr2O4 obtained in step (2) to obtain a synthesis gas catalyst.
[0031] The invention mixes zinc salt, chromium salt, TiO2 and water to obtain a mixed solution.
[0032] The present invention has no particular limitation on the particle size of the TiO2, and commercially available TiO2 powder can be used. In the embodiments of the present invention, the TiO2 used is analytically pure TiO2.
[0033] In the present invention, the zinc salt is preferably zinc nitrate or zinc chloride, more preferably zinc nitrate. In a specific embodiment of the present invention, the zinc nitrate used is zinc nitrate hexahydrate. The present invention limits the zinc salt to the above types, which is more conducive to the subsequent coprecipitation reaction.
[0034] In the present invention, the chromium salt is preferably chromium nitrate or chromium chloride, more preferably chromium nitrate. In a specific embodiment of the present invention, the chromium nitrate used is chromium nitrate nonahydrate. The present invention limits the chromium salt to the above types, which can be more conducive to the subsequent coprecipitation reaction.
[0035] In the present invention, the ratio of the amount of zinc salt, the amount of chromium salt, the amount of TiO2 and the volume of water is preferably (4.5-5.5) mol: (9-11) mol: (0.5-2) mol: (28-32) L, preferably (4.7-5.2) mol: (9.5-10.5) mol: (0.8-1.5) mol: (29-31) L, and more preferably 5 mol: 10 mol: 1 mol: 30 L. The present invention limits the ratio of the amount of zinc salt, the amount of chromium salt, the amount of TiO2 and the volume of water to the above range to obtain ZnCr2O4 with a suitable TiO2 doping amount.
[0036] The present invention has no special limitation on the mixing method and operation of the zinc salt, chromium salt, TiO2 and water. The raw materials can be mixed evenly using the method and operation well known to those skilled in the art.
[0037] After obtaining the mixed solution, the present invention mixes the mixed solution with a precipitant to perform a co-precipitation reaction, and then performs aging and calcination in sequence to obtain TiO2-doped ZnCr2O4.
[0038] In the present invention, the precipitant is preferably sodium carbonate or ammonium carbonate, more preferably ammonium carbonate; the precipitant is preferably used in the form of a solution; the concentration of the precipitant in the solution is preferably 0.4-0.7 mol / L, more preferably 0.5-0.6 mol / L, and further preferably 0.6 mol / L. The present invention limits the type, form of use and concentration of the precipitant to the above range to better control the speed of the coprecipitation reaction.
[0039] In the present invention, the mixing of the mixed solution and the precipitant is preferably carried out under stirring. As one embodiment of the present invention, a peristaltic pump can be used to simultaneously drop the mixed solution and the precipitant into a reaction container for mixing; the reaction container can be a three-necked flask; the three-necked flask can be equipped with a mechanical stirring device and a pH meter. The present invention does not have any special restrictions on the speed of the dripping, and it is sufficient to ensure that the pH value of the reaction liquid in the reaction container is between 5.5 and 8.5. The present invention does not have any special restrictions on the stirring speed set by the stirring device, and the stirring speed commonly used by those skilled in the art can be used. The above-mentioned mixing method is used in the present invention to better control the coprecipitation reaction.
[0040] As an embodiment of the present invention, during the mixing process, after the mixed solution is added dropwise, the precipitant is continued to be added dropwise to control the pH value of the reaction solution in the reaction container to be between 5.5 and 8.5.
[0041] In the present invention, the coprecipitation reaction is preferably carried out under the condition of water bath heating; the temperature of the coprecipitation reaction is preferably 50-80°C, more preferably 60-70°C; the pH value of the coprecipitation reaction is preferably 5.5-8.5, more preferably 6-7.5, and further preferably 6.5. The present invention limits the temperature and pH value of the coprecipitation reaction to the above ranges, which can be more conducive to the coprecipitation reaction.
[0042] In the present invention, after the coprecipitation reaction is completed, the reaction solution is preferably aged.
[0043] As an embodiment of the present invention, the aging temperature can be 50-80°C, or 60-70°C; the aging time can be 0.5-4h, or 1-3h, or 2h. The present invention can promote the crystal form perfection and crystal form transformation of the precipitate by aging the reaction solution, so that the crystalline precipitate forms uniform grains, and reduces impurities in the amorphous precipitate, thereby forming stable grains.
[0044] In the present invention, after aging, suction filtration is preferably performed to obtain a precipitate.
[0045] The present invention has no special limitation on the filtration operation, and the filtration operation well known to those skilled in the art can be used.
[0046] After obtaining the precipitate, the present invention preferably sequentially dries and calcines the precipitate to obtain TiO2-doped ZnCr2O4.
[0047] As an embodiment of the present invention, the drying temperature may be 70-110° C. The present invention has no particular limitation on the drying time, as long as the moisture in the precipitate can be removed.
[0048] As an embodiment of the present invention, the calcination temperature can be 400-600°C, or 500°C; the calcination time can be 3-5h, or 4h. The present invention limits the calcination temperature and time to the above ranges so that the catalyst can have a good catalytic effect.
[0049] After obtaining TiO2-doped ZnCr2O4, the present invention mixes SAPO-34 molecular sieve and TiO2-doped ZnCr2O4 to obtain a synthesis gas catalyst.
[0050] In an embodiment of the present invention, the preparation method of the SAPO-34 molecular sieve is: using pseudo-boehmite as an aluminum source, H3PO4 as a phosphorus source, and silica sol as a silicon source, pseudo-boehmite, H3PO4, silica sol, triethylamine (TEA) and water are mixed according to n(Al2O3):n(P2O5):n(SiO2):n(TEA):n(H2O)=1:0.95:0.1:3.5:75, and then hydrothermal crystallization and calcination are performed to obtain SAPO-34 molecular sieve; the calcination temperature is 650°C, and the calcination time is 5h. The SAPO-34 molecular sieve obtained by the above preparation method of the present invention can further improve the selectivity of the synthesis gas catalyst to light olefins.
[0051] In the present invention, the mass ratio of the SAPO-34 molecular sieve and the TiO2-doped ZnCr2O4 is preferably 1: (0.8-1.1), more preferably 1: (0.9-1.0), and further preferably 1: 1. The present invention limits the mass ratio of the SAPO-34 molecular sieve and the TiO2-doped ZnCr2O4 to the above range, so that the synthesis gas catalyst has a high CO conversion rate and a high light olefin selectivity.
[0052] The present invention has no special limitation on the mixing of the SAPO-34 molecular sieve and the TiO2-doped ZnCr2O4. The SAPO-34 molecular sieve and the TiO2-doped ZnCr2O4 can be uniformly mixed using a mixing method commonly used by those skilled in the art.
[0053] The present invention also provides the use of the synthesis gas catalyst described in the above technical solution or the synthesis gas catalyst prepared by the preparation method described in the above technical solution in preparing light olefins from synthesis gas.
[0054] In the present invention, the method for using the synthesis gas catalyst to prepare light olefins from synthesis gas comprises:
[0055] After the synthesis gas catalyst and quartz sand are mixed, hydrogen is introduced to reduce the mixture of the synthesis gas catalyst and quartz sand, and then the synthesis gas is introduced to prepare light olefins under the catalytic action of the synthesis gas catalyst.
[0056] As an embodiment of the present invention, the synthesis gas to produce light olefins is preferably carried out in a fixed bed microreactor.
[0057] As an embodiment of the present invention, the synthesis gas catalyst and quartz sand may be placed in a fixed bed reaction tube.
[0058] The present invention has no particular limitation on the mixing ratio of the synthesis gas catalyst and the quartz sand, and any mixing ratio known to those skilled in the art can be used. The present invention can improve the stability and reaction efficiency of the catalyst by mixing the synthesis gas catalyst and the quartz sand.
[0059] As an embodiment of the present invention, the flow rate of the hydrogen can be 15 mL / min; the purity of the hydrogen can be 99.99%. As an embodiment of the present invention, the temperature of the reduction can be 400° C.; the time of the reduction can be 8 hours. The present invention limits the flow rate of hydrogen and the reduction time to the above ranges, which can reduce the metal oxidation state in the catalyst to the metal active state, which is beneficial to the catalytic performance of the catalyst.
[0060] As an embodiment of the present invention, the synthesis gas may be a mixed gas of H2 and CO; the molar ratio of the H2 and CO may be 2:1.
[0061] As an embodiment of the present invention, the reaction temperature of the synthesis gas to light olefins can be 300-450°C; the reaction pressure of the synthesis gas to light olefins can be 1-2MPa; the GHSV of the synthesis gas to light olefins can be 5000-7000h -1 , can also be 6000h -1 The present invention sets the parameters in the process of preparing light olefins from synthesis gas to the above range, which can better play the role of the synthesis gas catalyst.
[0062] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0063] Example 1
[0064] A synthesis gas catalyst, comprising SAPO-34 molecular sieve and TiO2-doped ZnCr2O4;
[0065] The molar ratio of Zn element, Cr element and Ti element in the TiO2-doped ZnCr2O4 is 5:10:1;
[0066] The mass ratio of the SAPO-34 molecular sieve and the TiO2-doped ZnCr2O4 is 1:1;
[0067] The preparation method of the SAPO-34 molecular sieve is as follows: using pseudo-boehmite as an aluminum source, H3PO4 as a phosphorus source, and silica sol as a silicon source, pseudo-boehmite, H3PO4, silica sol, triethylamine (TEA) and water are mixed according to n(Al2O3):n(P2O5):n(SiO2):n(TEA):n(H2O)=1:0.95:0.1:3.5:75, and then hydrothermally crystallized and calcined to obtain the SAPO-34 molecular sieve; the calcination temperature is 650°C and the calcination time is 5 hours.
[0068] The preparation method of the synthesis gas catalyst is:
[0069] (1) 5 mol of zinc nitrate hexahydrate, 10 mol of chromium nitrate nonahydrate, 1 mol of TiO2 and 30 L of water are mixed to obtain a mixed solution;
[0070] (2) using a peristaltic pump, the mixed solution obtained in step (1) and 0.6 mol / L ammonium carbonate are simultaneously added dropwise to a three-necked flask equipped with a mechanical stirring device and a pH meter, and a coprecipitation reaction is carried out in a water bath at a temperature of 70° C. while maintaining the pH of the reaction solution at 6.5. After the reaction is completed, the reaction solution is aged at 70° C. for 3 h, and after the aging is completed, the reaction solution is filtered to obtain a precipitate, and the precipitate is dried at 90° C. and then calcined at 500° C. for 5 h to obtain TiO2-doped ZnCr2O4;
[0071] (3) The SAPO-34 molecular sieve and the TiO2-doped ZnCr2O4 obtained in step (2) are mixed and ground in a mass ratio of 1:1 to obtain a synthesis gas catalyst.
[0072] Comparative Example 1
[0073] The difference between Comparative Example 1 and Example 1 is that ZnCr2O4 is not doped with TiO2, and the rest is the same as Example 1.
[0074] Application Example 1
[0075] The synthesis gas catalyst in Example 1 is used to prepare light olefins from synthesis gas;
[0076] The method for using the synthesis gas catalyst to prepare light olefins from synthesis gas is as follows:
[0077] In a fixed bed microreactor, the synthesis gas catalyst and quartz sand in Example 1 were mixed in a mass ratio of 1:10 and placed in a fixed bed reaction tube. Hydrogen (purity of 99.99%) was introduced at a flow rate of 15 mL / min. The mixture of the synthesis gas catalyst and quartz sand was reduced at 400°C for 8 h and then synthesis gas (a mixture of H2 and CO, with a molar ratio of H2 to CO of 2:1) was introduced. The reaction temperature was 400°C, the reaction pressure was 2 MPa, and GHSV=6000 h-1 Preparation of light olefins from syngas under catalytic conditions.
[0078] The reaction products of the synthesis gas catalyst for preparing light olefins were analyzed and measured by gas chromatography. The conversion rate of CO to C2 in the synthesis gas catalyst of Application Example 1 was 25.1%. = ~C4 = The selectivity is 80.72%.
[0079] Comparative application example 1
[0080] The synthesis gas catalyst in Comparative Example 1 is used to prepare light olefins from synthesis gas, and the rest is the same as in Application Example 1.
[0081] The reaction products of the synthesis gas catalyst for preparing light olefins by catalytic synthesis gas were analyzed and measured by gas chromatography. The CO conversion rate of the synthesis gas catalyst in Application Example 1 was 20.5%, and the C2 = ~C4 = The selectivity was 74.03%.
[0082] The present invention dopes TiO2 into ZnCr2O4, and by controlling the doping amount of TiO2, the grain size of ZnCr2O4 can be refined, the dispersibility of the effective active component (ZnCr2O4) is improved, and the specific surface area and total pore volume of TiO2-doped ZnCr2O4 are increased, and the conversion rate of CO and the selectivity of low-carbon olefins of the synthesis gas catalyst are improved; SAPO-34 molecular sieve is used, and the ratio of SAPO-34 molecular sieve and TiO2-doped ZnCr2O4 is controlled to further improve the selectivity of low-carbon olefins of the synthesis gas catalyst. The synthesis gas catalyst provided by the present invention has a CO conversion rate of more than 25%, a C2 = ~C4 = The selectivity is greater than 80%, with high CO conversion rate and high light olefin selectivity.
[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A synthesis gas catalyst comprising SAPO-34 molecular sieve and TiO2-doped ZnCr2O4; The molar ratio of Zn element, Cr element and Ti element in the TiO2-doped ZnCr2O4 is (4.5-5.5): (9-11): (0.5-2); The mass ratio of the SAPO-34 molecular sieve to the TiO2-doped ZnCr2O4 is 1:(0.8-1.1).
2. The method for preparing the synthesis gas catalyst according to claim 1, comprising the following steps: (1) mixing zinc salt, chromium salt, TiO2 and water to obtain a mixed solution; (2) mixing the mixed solution obtained in step (1) with a precipitant to carry out a co-precipitation reaction, and then aging and calcining in sequence to obtain TiO2-doped ZnCr2O4; (3) Mixing the SAPO-34 molecular sieve and the TiO2-doped ZnCr2O4 obtained in step (2) to obtain a synthesis gas catalyst.
3. The preparation method according to claim 2, characterized in that: In the step (1), the volume ratio of the amount of zinc salt, the amount of chromium salt, the amount of TiO2 and water is (4.5-5.5) mol: (9-11) mol: (0.5-2) mol: (28-32) L.
4. The preparation method according to claim 2, characterized in that: In the step (2), the precipitant is sodium carbonate or ammonium carbonate.
5. The preparation method according to claim 4, characterized in that: The precipitant is used in the form of a solution.
6. The preparation method according to claim 5, characterized in that: The concentration of the precipitant in the solution is 0.4-0.7 mol / L.
7. The preparation method according to claim 2, characterized in that: The temperature of the coprecipitation reaction in the step (2) is 50-80° C., and the pH value of the coprecipitation reaction is 5.5-8.
5.
8. The preparation method according to claim 2, characterized in that: The aging temperature in step (2) is 50-80° C., and the aging time is 0.5-4 h.
9. The preparation method according to claim 2, characterized in that: In the step (2), the calcination temperature is 400-600° C., and the calcination time is 3-5 hours.
10. Use of the synthesis gas catalyst according to claim 1 or the synthesis gas catalyst prepared by the preparation method according to any one of claims 2 to 9 in preparing light olefins from synthesis gas.